Macrocurrent and microcurrent electrostimulation in sport - Siff, M. C. (Supertraining, 1999)
The use of electric current on the human body largely has been restricted to use by physiotherapists to facilitate the healing of musculoskeletal injuries and control pain. It is fairly arbitrarily applied in two broad categories: